2003
DOI: 10.1037/0278-6133.22.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias predicts outcome in smoking cessation.

Abstract: Most attempts to quit smoking end in failure, with many quitters relapsing in the first few days. Responses to smoking-related cues may precipitate relapse. A modified emotional Stroop taskwhich measures the extent to which smoking-related words disrupt performance on a reaction time (RT) task-was used to index the distracting effects of smoking-related cues. Smokers (N = 158) randomized to a high-dose nicotine patch (35 mg) or placebo patch completed the Stroop task on the 1st day of a quit attempt. Smokers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
313
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(331 citation statements)
references
References 67 publications
(105 reference statements)
12
313
2
4
Order By: Relevance
“…Longer interference scores for emotion-laden words are interpreted as a preoccupation with the drugrelated stimuli. Increased interference time for drug-related words has been shown in subjects with dependence on cocaine (Copersino et al, 2004;Carpenter et al, 2006;Hester et al, 2006), alcohol (Bauer and Cox, 1998;Cox et al, 2002;Lusher et al, 2004), heroin (Franken et al, 2000), and nicotine (Gross et al, 1993;Wertz and Sayette, 2001;Waters et al, 2003). It has been proposed that this preoccupation with drug-related stimuli is a form of attentional bias thought to underlie relapse (Franken, 2003;Copersino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Longer interference scores for emotion-laden words are interpreted as a preoccupation with the drugrelated stimuli. Increased interference time for drug-related words has been shown in subjects with dependence on cocaine (Copersino et al, 2004;Carpenter et al, 2006;Hester et al, 2006), alcohol (Bauer and Cox, 1998;Cox et al, 2002;Lusher et al, 2004), heroin (Franken et al, 2000), and nicotine (Gross et al, 1993;Wertz and Sayette, 2001;Waters et al, 2003). It has been proposed that this preoccupation with drug-related stimuli is a form of attentional bias thought to underlie relapse (Franken, 2003;Copersino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the abstinent session was re-scheduled. Participants completed: 1) A startle probe assessment, as described below; 2) A second startle probe assessment (participants either smoked a cigarette (S) or rested (NS) between the two startle assessments); 3) The Brief Questionnaire of Smoking Urges (QSU-brief; Cox et al, 2001) and the Positive and Negative Affect Schedule (PANAS; Watson et al, 1988); 4) The computerized smoking Stroop task (Waters et al, 2003) and the Subjective Stroop Questionnaire (SSQ) (data will be reported in detail elsewhere2); 5) The QSU-brief, PANAS again; 6) The IAT; 7) Five items assessing outcome expectations from smoking (described below). All questionnaires were administered by computer.…”
Section: Methodsmentioning
confidence: 99%
“…Human drug addiction is a complex multifactorial phenomenon that features, with remarkable consistency, a difficulty in directing attention away from salient drug-related stimuli. Behavioral studies have shown that processing a nonsalient stimulus in the presence of a salient drug-related stimulus presents a significant difficulty for those dependent on cocaine (Copersino et al 2004;Hester et al 2006), alcohol (Sharma et al 2001;Ryan 2002;Cox et al 2003;Duka and Townshend 2004a, b), cannabis (Field et al 2004a), nicotine (Wertz and Sayette 2001;Powell et al 2002;Waters et al 2003;Bradley et al 2004;Field et al 2004b), or heroin (Lubman et al 2000;Franken et al 2003). Similarly, electrophysiological studies, which are able to directly quantify the allocation of processing resources to specific stimuli independently of conscious awareness, demonstrate enhanced event-related potential (ERP) responses to drugrelated stimuli compared to nonsalient stimuli across a range of addicted populations (Warren and McDonough 1999;Herrmann et al 2000Herrmann et al , 2001Franken et al 2003;van de Laar et al 2004;Lubman et al 2007b.…”
Section: Attentional Bias For Drug-related Stimulimentioning
confidence: 99%
“…While the relationship between craving and relapse during abstinence is complex, users typically report that cravings occur prior to and during the period of highly ritualized and automatic drug-taking behavior that follows an impulsive urge to use (Miller and Gold 1994). Recent studies have demonstrated that the extent of an individual users' attentional bias for drug-related stimuli can robustly predict the likelihood of successfully ceasing cigarette smoking (Waters et al 2003), or remaining abstinent during treatment for alcohol (Cox et al 2002), cocaine (Carpenter et al 2005), and heroin (Marissen et al 2006) dependence. The study by Cox et al (2002) measured attentional bias for alcohol-related stimuli over two time-points and demonstrated that levels of bias increased prior to relapse.…”
Section: Attentional Bias For Drug-related Stimulimentioning
confidence: 99%